Secondary Spontaneous Tension Pneumothorax: A Case Report of an Uncommon Presentation of Post-Tuberculosis Sequelae - Willim, Herick Alvenus (The New Ropanasuri Journal of Surgery, 2023)
Introduction. Tuberculosis (TB) remains one of the top life-threatening infectious diseases worldwide. Even after completion of treatment, numerous patients had post-TB sequelae as a consequence of lung damage during TB infection. We reported an uncommon case of secondary spontaneous tension pneumothorax in a patient with post-TB sequelae. Case Presentation. A 68-year-old smoker man presented with sudden shortness of breath since 2 hours ago. He had a history of pulmonary TB 15 years ago which had completed antituberculosis treatment and had been experiencing symptoms associated with post-TB sequelae for the last 1 year. Physical examinations and chest X-ray showed tension pneumothorax. The recent GeneXpert sputum test showed a negative result for Mycobacterium tuberculosis. We performed urgent needle decompression, followed by chest tube insertion. He responded well to the treatment and was discharged after the seventh day with no residual pneumothorax. Conclusion. Spontaneous tension pneumothorax in patients with post-TB sequelae is rare and has a complex pathogenesis. It may include several factors including pulmonary fibrosis, pleural adhesion, ruptured open healed cavity or bullae, and lung damage from cigarette smoking. It should be managed by urgent needle decompression followed by chest tube thoracostomy.